Elección del Sistema de explotación para la extracción de materiales de construcción en el área minera 'Jesús del Gran Poder' bajo el régimen de pequeña minería, código 600727, sector Agua Dulce, cantón Calvas, provincia de Loja - Carrión Torres, Adrián José (2025)
This study presents a mining exploitation design focused on extracting construction materials from the "Jesús del Gran Poder" concession, located in Calvas canton, Loja province, and operated under small-scale mining regulations. By analyzing the geological and topographical conditions of the area—spanning approximately 104,520.673 m² with steep slopes (ranging from 22.8% to 24.2%) and elevations between 1610.7 and 1701 meters above sea level—critical factors for project design and planning were identified. These characteristics necessitate an exploitation approach tailored to maximize performance and ensure long-term sustainability. The geological survey identified two main units within the area: the El Fundo Unit (Pliocene) and the Changaimina Unit (Upper Cretaceous), consisting of andesitic lavas and mudflow deposits. Subsequently, laboratory tests were conducted on representative samples, evaluating abrasion, granulometry, California Bearing Ratio (CBR), and Standard Proctor tests, in compliance with the Ministry of Transportation and Public Works (MTOP) standards. The results confirmed the suitability of the materials for construction purposes. Material reserves were estimated using the cross-section method, yielding a total volume of 2,787,380.403 m³, classified into proven reserves (1,114,952.161 m³), probable reserves (1,672,428.242 m³), and possible reserves, which allowed for the definition of optimal intervention zones. Based on the deposit's characteristics, open-pit mining was identified as the most appropriate method, implemented under a "Descending excavation and abandonment of the slope in final benches" scheme, optimizing both safety and efficiency in steep terrain. The proposed design increases the daily production capacity from 155 m³/day to 420.70 m³/day by expanding operational cycles and daily working hours. This scheme projects positive profitability from the fourth month onward, supported by the demand for materials in Calvas canton. The findings of this research demonstrate high potential for sustainability and economic feasibility, contributing to regional development through responsible and controlled exploitation. Key Words: Mining exploitation, geology, construction materials, responsible mining